Application of a two-step approach for mapping ice thickness to various glacier types on Svalbard - Fürst, Johannes; Gillet-Chaulet, Fabien; Benham, Toby; Dowdeswell, Julian; Grabiec, Mariusz; Navarro, Francisco J.; Pettersson, Rickard; Moholdt, Geir; Nuth, Christopher; Saß, Björn; Aas, Kjetil; Fettweis, Xavier; et al. (Cryosphere, 2017)
The basal topography is largely unknown beneath most glaciers and ice caps, and many attempts have been made to estimate a thickness field from other more accessible information at the surface. Here, we present a two-step reconstruction approach for ice thickness that solves mass conservation over single or several connected drainage basins. The approach is applied to a variety of test geometries with abundant thickness measurements including marine- and land-terminating glaciers as well as a 2400 km2 ice cap on Svalbard. The input requirements are kept to a minimum for the first step. In this step, a geometrically controlled, non-local flux solution is converted into thickness values relying on the shallow ice approximation (SIA). In a second step, the thickness field is updated along fast-flowing glacier trunks on the basis of velocity observations. Both steps account for available thickness measurements. Each thickness field is presented together with an error-estimate map based on a formal propagation of input uncertainties. These error estimates point out that the thickness field is least constrained near ice divides or in other stagnant areas. Withholding a share of the thickness measurements, error estimates tend to overestimate mismatch values in a median sense. We also have to accept an aggregate uncertainty of at least 25 % in the reconstructed thickness field for glaciers with very sparse or no observations. For Vestfonna ice cap (VIC), a previous ice volume estimate based on the same measurement record as used here has to be corrected upward by 22 %. We also find that a 13 % area fraction of the ice cap is in fact grounded below sea level. The former 5 % estimate from a direct measurement interpolation exceeds an aggregate maximum range of 6–23 % as inferred from the error estimates here.

Imprints of climate signals in a 204 year δ18O tree-ring record of nothofagus pumilio from Perito Moreno Glacier, Southern Patagonia (50◦S) - Grießinger, Jussi; Langhamer, Lukas; Schneider, Christoph; Saß, Björn; Steger, David; Skvarca, Pedro; Braun, Matthias; Meier, Wolfgang; Srur, Ana M.; Hochreuther, Philipp (Frontiers in Earth Science, 2018)
A 204 year-long record of delta O-18 in tree-ring cellulose of southern beech (Nothofagus pumilio) from a site near Perito Moreno Glacier (50:S) in Southern Patagonia was established to assess its potential for a climate reconstruction. The annually resolved oxygen isotope chronology is built out of seven individual tree-ring delta O-18 series with a significant mean inter-series correlation (r = 0.61) and is the first of its kind located in Southern America south of 50 degrees S. Over a common period from 1960 to 2013 of available stationary and high-resolution gridded CRU TS v. 4.01 data, the delta O-18 chronology exhibits a strong sensitivity toward hydroclimatic as well as temperature parameters as revealed by correlation analyses. Among these, positive correlations with maximum temperature in the first part of the summer season (CRU r(ONDJ) = 0.51, p < 0.01) and negative correlations with precipitation in the latter half of the vegetation period (CRU r(ONDJ) = -0.54, p < 0.01) show the highest sensitivities. A strong supra-regional influence of the Southern Annular Mode (SAM) is clearly recorded in this chronology as indicated by significant positive correlations during the vegetation period (r(ONDJ) = 0.62, p < 0.01). This indicates that the presented delta O-18-chronology shows great promise to reconstruct the influence and variability of the SAM within the last two centuries in southern South America. The modulation of positive and negative anomalies within this series can be interlinked to changes in moisture source origin as revealed by backward trajectory modeling. Additionally, these anomalies can be directly associated to positive or negative phases of the Antarctic Oscillation Index (AAOI) and therefore the strength of the Westerlies. Aligned by the analysis on the influence of different main weather types on the delta O-18 chronology it is shown that such time-series hold the potential to additionally capture their respective influence and change during the last centuries.
Keywords: Backward trajectory modeling; Perito Moreno Glacier; Southern Annular Mode (SAM); Main weather types; Nothofagus pumilio; Southern Patagonia; Tree-ring δ18O